2000
DOI: 10.1038/79534
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial chemoprevention of intestinal neoplasia

Abstract: A combination of two drugs afforded remarkable protection from intestinal neoplasia in APC(Min/+) mice, a murine model of human familial adenomatous polyposis (FAP). One of the drugs was sulindac, a prototypical non-steroidal anti-inflammatory drug with established chemopreventative activity. The second drug was EKI-569, a newly developed, irreversible inhibitor of the epidermal growth factor receptor kinase. Although 100% of the untreated APC(Min/+) mice developed approximately 20 polyps, nearly half the mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
249
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 459 publications
(264 citation statements)
references
References 39 publications
12
249
0
2
Order By: Relevance
“…Furthermore, trastuzumab does not induce apoptosis in breast cancer cells, but it is able to increase the ZD1839-induced programmed cell death . In addition, a recent report has shown that EGFR-TKIs increase the ability of non-steroidal antiinflammatory drugs to prevent the formation of intestinal polyps in an experimental murine model of human familial adenomatous polyposis (FAP) (Torrance et al, 2000). Taken together, these observations suggest that combination of different target-based agents might prove extremely efficient in inhibiting the growth of human solid malignancies.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, trastuzumab does not induce apoptosis in breast cancer cells, but it is able to increase the ZD1839-induced programmed cell death . In addition, a recent report has shown that EGFR-TKIs increase the ability of non-steroidal antiinflammatory drugs to prevent the formation of intestinal polyps in an experimental murine model of human familial adenomatous polyposis (FAP) (Torrance et al, 2000). Taken together, these observations suggest that combination of different target-based agents might prove extremely efficient in inhibiting the growth of human solid malignancies.…”
Section: Discussionmentioning
confidence: 95%
“…To facilitate examination of the colon, tissue samples were "Swiss rolled" prior to embedding and sectioning. 21 Cecal and colon sections were graded for inflammation using a scale of 0 (no inflammation), +1 (mild increase in inflammatory cells; no mucosal changes), +2 (moderate increase in inflammatory cells; mild scattered proliferation +/− focal loss of crypt architecture), +3 (severe increase in inflammatory cells; diffuse or nearly diffuse proliferation, focally extensive loss of crypt architecture), +4 (complete or nearly complete mucosal destruction).…”
Section: Histologymentioning
confidence: 99%
“…The above molecules have been shown to synergise in vitro and in animal models the effects of conventional anticancer agents (Ciardiello et al, 2000). First, treatments based on combination therapy with NSAIDs and compounds that target other oncogenic pathways have been successfully tested in chemopreventive settings: Torrance et al (2000) showed that combination treatment of APCmin mice with sulindac and the ErbB tyrosine kinase inhibitor EKI-569 resulted in synergistic antitumour activity that leads to complete polyp prevention in half of all treated mice. Then, DuBois and collaborators, in the field of cancer therapy, clearly showed that the combination of celecoxib and herceptin had additive effects against the HCA rectal adenocarcinoma cell line in vitro and in xenograft, which leads to the almost complete inhibition of tumour growth (Mann et al, 2001).…”
Section: Further Attractive Combination Therapymentioning
confidence: 99%